2019
DOI: 10.1016/j.jemermed.2019.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular Accident in a Pediatric Patient Presenting With Influenza

Abstract: Background: Acute ischemic stroke (AIS) in pediatric populations accounts for more than half of pediatric strokes and is associated with significant morbidity and mortality. Pediatric AIS can present with nonspecific symptoms or symptoms that mimic alternate pathology. Case Report: A 4-month-old female presented to the emergency department for fever, decreased oral intake, and ''limp'' appearance after antibiotic administration. She was febrile, tachypneic, and hypoxic. Her skin was mottled with 3-s capillary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Cerebrovascular accidents are very rarely associated with influenza in children, with authors claiming that their 2019 case was only the third ever reported (20).…”
mentioning
confidence: 99%
“…Cerebrovascular accidents are very rarely associated with influenza in children, with authors claiming that their 2019 case was only the third ever reported (20).…”
mentioning
confidence: 99%